2016
DOI: 10.1016/j.ijmedinf.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of speech recognition errors in the emergency department

Abstract: This is the first estimate at classifying speech recognition errors in dictated emergency department notes. Speech recognition errors occur commonly with annunciation errors being the most frequent. Error rates were comparable if not lower than previous studies. 15% of errors were deemed critical, potentially leading to miscommunication that could affect patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
(24 reference statements)
0
6
0
1
Order By: Relevance
“…Clinicians face pressure to decrease documentation time and often only superficially review their notes before signing them. 9 Fully shifting the editing responsibility from transcriptionists to clinicians may lead to increased documentation errors if clinicians are unable to adequately review their notes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians face pressure to decrease documentation time and often only superficially review their notes before signing them. 9 Fully shifting the editing responsibility from transcriptionists to clinicians may lead to increased documentation errors if clinicians are unable to adequately review their notes.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation errors can put patients at significant risk of harm. 9 An analysis of medical malpractice cases found that incorrect information (eg, faulty data entry) was the top EHR-related contributing factor, contributing to 20% of reviewed cases. 10,11 It is therefore in the best interest of both patients and clinicians that medical documents be accurate, complete, legible, and readily accessible for the purposes of patient safety, health care delivery, billing, audit, and possible litigation proceedings.…”
Section: Introductionmentioning
confidence: 99%
“…In 6 von 10 Studien (siehe ▶ Tab. 2) zeigte sich bei der Analyse der Fehlerrate die Spracherkennungstechnologie im Vergleich zu einem Schreibdienst oder der Texteingabe als nicht überlegen [23], [24], [25], [26], [27], [28], [29], [30]. Die mit Spracherkennungstechnologie erstellten medizinischen Berichte enthielten im Durchschnitt der Studien eine um den Faktor 1,5 erhöhte Fehlerrate als bei Erstellung durch eine Schreibkraft, was mit einer Verlängerung der Doku- mentationszeit einhergehen kann [19].…”
Section: Analyse Der Genauigkeit Und Der Fehlerrateunclassified
“…Given the necessity of seeking solutions that will not degrade the clinical workflow, technology solutions using automatic speech recognition (ASR) have been explored for hands-free clinical documentation [20][21][22][23]. A mobile platform based on ASR technologies has the potential to enable hands-free documentation by extracting medical information from the incoming audio stream without hand-operated input devices.…”
Section: Introductionmentioning
confidence: 99%